DIAGNOSTIC LAPAROSCOPY IN MAYER-ROKITANSKY-KÜSTER-HAUSER SYNDROME : A CASE REPORT - Putri Irmayani; Nona Suci Rahayu; Zulkarnaini (PT. Radja Intercontinental Publishing, 2024)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a congenital condition resulting from Müllerian agenesis, characterized by the absence or underdevelopment of the uterus and upper two-thirds of the vagina, while maintaining a normal female phenotype and karyotype (46,XX). This case report details the presentation, diagnosis, and management of a 24-year-old female patient with primary amenorrhea due to MRKH syndrome. The patient presented with typical secondary sexual characteristics and an absence of menstruation. Diagnostic imaging, including ultrasonography and laparoscopy, confirmed the absence of the uterus and the presence of normal ovaries and fallopian tubes, consistent with Type I MRKH syndrome. Management options, including reproductive counseling and vaginal reconstruction techniques, were discussed to address the patient’s physical and psychological well-being. Surgical exploration ruled out other associated anomalies. This case highlights the importance of early diagnosis, multidisciplinary management, and patient counseling to improve quality of life and provide clarity regarding reproductive possibilities for MRKH patients.